Transformation from manufacturing process taxonomy to repair process taxonomy: A phenetic approach - Umair Raza; Wasim Ahmad; Atif Khan (Journal of Industrial Engineering International, 2018)
The need of taxonomy is vital for knowledge sharing. This need has been portrayed by through-life engineering services/systems. This paper addresses this issue by repair process taxonomy development. Framework for repair process taxonomy was developed followed by its implementation. The importance of repair process taxonomy has been highlighted.
Keywords: 650; Through-life engineering; Knowledge sharing